Immunohistochemical Analysis of Mismatch Repair Deficiency in Colorectal Cancer Patients in Kuantan, Pahang - F., Muhammad Ishaque; H., Asmah Hanim; A.T., Norlelawati; A, Nor Zamzila; E., Feisal; S., Arfahiza (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: The deficient mismatch repair (dMMR) status of colorectal cancer (CRC) is the hallmark of a defective DNA mismatch repair (MMR) system. Immunohistochemistry (IHC) indirectly detects the affected gene by the loss of its protein product. This study aimed to assess the frequency of different types of dMMR status and associate them with the clinicopathological characteristics of CRC patients diagnosed at Hospital Tengku Ampuan Afzan (HTAA) and the Sultan Ahmad Shah Medical Centre (SASMEC) using an immunohistochemical method. MATERIAL AND METHODS: Formalin-fixed paraffin-embedded (FFPE) tissue blocks of 123 CRC cases were retrieved from the Pathology Department of HTAA and SASMEC for patients diagnosed between 1 January 2017 and 31 December 2018. IHC was performed manually using an Envision Flex Polymer detection kit (Dako) along with four primary anti-mouse antibodies (MLH1, PMS2, MSH2, and MSH6) for the MMR proteins to assess dMMR status. RESULTS: Out of 123 cases, 21 (17.07%) showed the loss of one or more MMR protein expression and were dMMR. There was no statistically significant association between pMMR (proficient Mismatch repair) and dMMR cases with regards to clinicopathological factors (age, sex, race, site of the tumour, TNM (Tumour Node Metastasis) staging, bowel wall invasion, lymph node metastasis, lymphovascular invasion, histological type, and tumour differentiation). CONCLUSION: IHC is the preferred method and most reproducible test for assessing dMMR status in CRC patients in the histopathology diagnostic laboratory.